Problems of Economic Activity Management of Household - M. M. Khaykin (Управление)
The article considers the basic constituents of economic activity of household: legal; administrative; production; marketing; commercial; financial; infrastructural types of activity. The special attention is paid to the role of modern processes of transformation of institutional environment in maintenance and character of made decision in the sector of household.